Potential Antagonistic Interactions of Cassia alata L. Leaf Extract and Commercial Antibiotics against Staphylococcus aureus: An In Vitro Evaluation - Oki Rokhim Mawakhid; Putri Ramanda; Samuel Billie Tua Sinaga; Winda Shari; Avidlyandi Avidlyandi; Khafit Wiradimafan; Salprima Yudha S.; Risky Hadi Wibowo; Morina Adfa (Jurnal Penelitian Pendidikan IPA, 2026)
Several in vitro studies have demonstrated that the combination of plant extracts with antibiotics may reduce the minimum inhibitory concentration (MIC) of antibiotics against resistant microorganisms. Interactions between plant extracts and antibiotics can be synergistic, additive, or antagonistic. This study aimed to evaluate the potential interaction between Cassia alata leaves methanol extract and five selected conventional antibiotics in inhibiting the growth of Staphylococcus aureus ATCC 29213. Antibacterial activity was assessed using the well diffusion and paper strip methods. The methanol extract of C. alata leaves, when tested singly at a concentration of 100 mg/mL, produced an average inhibition zone of 11.74 mm. Four antibiotics, namely ciprofloxacin, clindamycin, chloramphenicol, and tetracycline, exhibited stronger antibacterial activity with inhibition zones ranging from 19.56–27.26 mm, whereas co-trimoxazole showed no inhibitory effect. The combination of C. alata leaves methanol extract with ciprofloxacin, clindamycin, chloramphenicol, tetracycline, and cotrimoxazole resulted in inhibition zones of 22.26 ± 0.703 mm, 22.54 ± 1.222 mm, 17.91 ± 1.094 mm, 17.57 ± 0.652 mm, and 9.30 ± 1.180 mm, respectively. The combined treatments have potential antagonistic effects, as the inhibition zones were smaller than the sum of the individual activities of the extract and antibiotics. Therefore, the combination was considered less effective in suppressing growth of S. aureus ATCC 29213